2010
DOI: 10.1108/03684921011062746
|View full text |Cite
|
Sign up to set email alerts
|

Modeling service experience design processes with customer expectation management

Abstract: Purpose-This paper proposes a conceptual framework of customer expectation management and a reference model of service experience design which are regarded as the basic foundation to model the processes of experience design for service operation strategies simulating and testing by employing a system dynamics approach. Design/methodology/approach-System dynamics is the key approach which includes causal loop diagram (CLD) and stock and flow diagram (SFD) used to build the reference model of experience design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…The increase in customer expectation is due to the increase in customer satisfaction, perceived product quality and customer product knowledge (all of the estimated parameters: 1.110, 1.208, 2.358, have a positive sign). The model also shows that customer expectation negatively correlates with business competitiveness, which is inconsistent with the research by Yuan Hsieh, who identified a positive correlation (Hsieh & Yuan, 2010). The estimated correlation is, however, weak (À0.064), and is also not statistically significant (see Table A2 in the appendix).…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…The increase in customer expectation is due to the increase in customer satisfaction, perceived product quality and customer product knowledge (all of the estimated parameters: 1.110, 1.208, 2.358, have a positive sign). The model also shows that customer expectation negatively correlates with business competitiveness, which is inconsistent with the research by Yuan Hsieh, who identified a positive correlation (Hsieh & Yuan, 2010). The estimated correlation is, however, weak (À0.064), and is also not statistically significant (see Table A2 in the appendix).…”
Section: Resultscontrasting
confidence: 92%
“…This division is considered to be appropriate for investigating general customer satisfaction, where there is an examination of overall customer satisfaction with the purchase of a product over the long term, when the customer buys the product repeatedly. This leads to mutual interaction between the variables where the causes then become effects, and the effects become the causes, as suggested by Hsieh and Yuan (2010). It is possible, therefore, to define three basic equations 2 representing three hypotheses, and simultaneously form a model of the relationship between the variables pertaining to customer satisfaction:…”
Section: Model Constructionmentioning
confidence: 99%
“…Customer expectation is multifaceted and capricious. Service provider should learn what a customer expect in order to deliver a good service (Hsieh & Yuan, 2010); (3) perceived value. Zeithaml (1988) defines perceived value as, ''The consumer's overall assessment of the utility of a product (or service) based on perceptions of what is received and what is given''; (4) customer satisfaction; (5) customer complaints.…”
Section: National Satisfaction Indexmentioning
confidence: 99%
“…These models have proved to be an effective means of establishing how complex systems function, and, as such, are being actively applied (Dacko 2010;Ahmed and Prashar 2010;Hsieh and Yuan 2010).…”
Section: Introductionmentioning
confidence: 99%